Study of Learning Motivation of Students of Educational Technology Students During The Covid-19 PandemiDY OF LEARNING MOTIVATION OF STUDENTS OF EDUCATIONAL TECHNOLOGY STUDENTS DURING THE COVID-19 PANDEMI - Mabrun, Kevin Juan; Apriani, Leni (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2022)
Motivation is one of the characteristics and psychological skills that determine the success of student learning outcomes. The problems that occur in online physical education learning during the covid pandemic have raised the issue of lack of motivation so that learning outcomes are not optimal. In the last 2-3 years, during the COVID-19 pandemic, motivation has been widely cited as a determinant of student learning success. This study aims to review and examine providing an overview of the results of a literature review regarding motivation in online physical education learning during the COVID-19 pandemic. This research is a qualitative type with a PISTKA study approach, which means conducting an external study from the results of previous studies that have been published with the theme of student physical education learning motivation during the COVID-19 pandemic. The results of the literature review are expected to be able to be used as studies or information that can be used as a theoretical basis for further research in handling student learning motivation during the COVID-19 pandemic so as to produce optimal learning success